SPECIFIC FEATURES OF INNOVATION PROCESS CREATION AND DEVELOPMENT IN AGRIBUSINESS - Valerу Mikhailovich Khabarov (Advanced Engineering Research)
The operational and industry characteristics of the creation and development of the innovation process in the agribusiness are defined. The situation in this field is described as rather acute. To a large extent, it is caused by the transition deformations. The innovation process is considered by the author as a related research and development, design, and experimental work follow-up. The works are aimed at the manufacture and introduction of new products and technologies. The innovation process is characterized by the system-based, cyclic, probabilistic nature, social and environmental significance. The primary strategic directions of the innovative processes in accordance with the agribusiness functional and industry characteristics are considered. The stepwise implementation of the given directions will allow both the agrobusiness restoration, and the country food sovereignty provision. Besides, the innovation process development will facilitate the gradual possibility for the entrance of the Russian Federation to the world market as an exporter of agricultural commodities.